Effect of initial variance of microstructures on grain growth under mean curvature. (20th June 2017) - Baskaran, Arun; Crist, David; Lewis, Daniel
Abstract: Surface Evolver was used to simulate grain growth under motion by mean curvature starting with non-uniform microstructures. The study was conducted for different microstructures that begin evolving with an identical mean grain area and a differing value of statistical variance of the grain areas. Correlation between a microstructure's initial variance, a geometric property of the polycrystalline network, and its growth rate in the normal regime was studied. It was observed that the microstructures evolved at different growth rates. The microstructures with the largest and smallest variances evolved with highest and lowest growth rates. The analysis was performed in the normal grain growth regime. It is observed that a direct correlation can be made between the initial variance of the microstructure and its growth rate in the normal regime. These results highlight the importance of including the grain size variance when controlling microstructure using non-uniform thermal fields.